Inovasi Pelayanan Administrasi Kependudukan di Kabupaten Gorontalo - Walahe, Dewi; Podungge, Abdul Wahab; Tabo, Sarfan; Polingapo, Jefri (Jurnal Kebijakan Publik, Ilmu Administrasi, 2025)
Population administration services are a fundamental aspect in the implementation of transparent and accountable governance. In Gorontalo Regency, the increasing need for population document services encourages the Population and Civil Registration Office to develop various innovations, such as pick-up services, document digitization, and the Independent Dukcapil Pavilion. The main problems faced include low public awareness, limited facilities, and geographical challenges that hinder the equitable distribution of services. This study aims to analyze the implementation of population administration service innovations and the factors that affect them. The method used is a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. Data analysis was carried out using the interactive model Miles, Huberman, and Saldaña (2014), which included condensation, presentation, and drawing data conclusions. The results of the study show that service innovations in Gorontalo Regency have increased public access to population documents, although they are still constrained by limited infrastructure and public administration literacy. The research findings confirm the importance of collaboration between individuals, organizations, and society in the success of innovation. The implications of this study show that the sustainability of public innovation requires strengthening the capacity of human resources and technological support. This research is important as an empirical contribution to the development of public service innovation in the regions, as well as opening up opportunities for further research on the effectiveness and social impact of population innovation in Indonesia.